1.4k views
4 votes
PLZ HELP 40 MINUTES LEFT

Which equation can be used to represent the statement?

The sum of one-sixth of a number and negative two is equal to negative two-thirds.
One-sixth + n = negative 2 + two-thirds
One-sixth + n = negative 2 + (negative two-thirds)
One-sixth n + 2 = negative two-thirds
One-sixth n minus 2 = negative two-thirds

1 Answer

4 votes

Answer:

It's the last one: One-sixth n minus 2 = negative two-thirds

Explanation:

Hope this helps!!

User PoorInRichfield
by
5.4k points